2017
DOI: 10.1590/2358-2936e2017003
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive strategy of the shrimp Nematopalaemon schmitti (Decapoda, Caridea, Palaemonoidea) on the southeastern coast of Brazil

Abstract: BraZIlIan crustacean socIety This article is part of the special series offered by the Brazilian Crustacean Society in honor to Nilton José Hebling in recognition of his dedication and contributions to the development of carcinology in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In terms of reproductive strategy, several factors may explain this size distribution, as fecundity and investment per gamete are positively correlated with female size in many shrimp species, and this trait may be advantageous in maximizing fitness (Berglund, 1981;Nye & Copley, 2014). This was corroborated by Pereira et al (2017), who found a positive relationship between carapace length and the number of embryos in N. schmitti sampled outside (Ubatuba-São Paulo State) the Cabo Frio upwelling area. According to Wickler and Seibt (1981) and Bauer (2004), this size pattern is common in carideans in which the mating system is pure searching (promiscuous).…”
Section: F I G U R Ementioning
confidence: 84%
See 1 more Smart Citation
“…In terms of reproductive strategy, several factors may explain this size distribution, as fecundity and investment per gamete are positively correlated with female size in many shrimp species, and this trait may be advantageous in maximizing fitness (Berglund, 1981;Nye & Copley, 2014). This was corroborated by Pereira et al (2017), who found a positive relationship between carapace length and the number of embryos in N. schmitti sampled outside (Ubatuba-São Paulo State) the Cabo Frio upwelling area. According to Wickler and Seibt (1981) and Bauer (2004), this size pattern is common in carideans in which the mating system is pure searching (promiscuous).…”
Section: F I G U R Ementioning
confidence: 84%
“…Shrimps are an important link between primary production and higher trophic levels (Kikuchi, 1966;Unsworth et al, 2007), and such information can assist in responsible planning for the conservation of species. Studies involving N. schmitti have been conducted in Brazil, including its ecological distribution (Almeida et al, 2012;Fransozo et al, 2009;Herrera et al, 2017), population structure (Almeida et al, 2011), fecundity and reproductive investment (Pereira et al, 2017) and relative growth and morphological sexual maturity (Herrera et al, 2018). Despite these studies, there is still a knowledge gap about assessing the reproductive parameters of species in a region with unusual features such as upwelling.…”
mentioning
confidence: 99%
“…Pereira et al. (2017) found that N. schmitti has continuous reproduction throughout the year. Thus, N. schmitti could promote recruitment all year‐round.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the reproductive biology of palaemonid prawns is an important tool to establish biodiversity conservation strategies (Mossolin & Bueno, 2002). Reproductive characteristics may vary according to individual intrinsic aspects, such as female size and age, as well as according to environmental conditions, and may influence fertility and recruitment (Sastry, 1983;Pereira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%